Determination of rice accession status using infochemical and visual cues emitted to sustainably control diopsis apicalis dalman - Bocco, R.; Pegalepo, E.; Togola, A.; Nwilene, F.E.; Bernard, G.C.; Zoclanclounon, Y.A.B.; Ndjiondjop, M.; Sow, M.; Kim, J.J.; Tamò, Manuele (MDPI, 2025)
This study assessed the host plant selection behavior of female stalk-eyed flies (SEFs) or Diopsis apicalis, where a Y-tube olfactometer was used to compare SEF attraction to the odor of leaves from four rice varieties (ITA306, WAB56-104, CG14, and RAM55). Another step of the evaluation consisted of pairing leaf odors from two rice varieties. Also, potted plants of the tested varieties were displayed in a screened cage and submitted to female SEF selection. The results indicated that the odor produced by leaves from rice varieties CG14, WAB56-104, and ITA306 significantly attracted SEFs, at rates of 81%, 70%, and 97%, respectively, while SEF females were rarely attracted by the odor of leaves from the resistant rice variety RAM55, at a rate of 35%. The results suggested that the use of a Y-tube olfactometer was similar to the use of a screened cage. The resistance exhibited by rice variety CG14 against SEFs is related to an antibiosis interaction acting as bait, while that in RAM55 is an antixenosis one. Farmers can plant the traditional CG14 variety on the edge of rice fields to draw SEFs and poison their larvae. However, RAM55 can be inserted in an intercropping system to repel SEFs from laying eggs. The authors recommend CG14 and RAM55 as candidates for breeding to create resistant lines against SEF.